Counseling on The Technology of Processing Quail Feces Waste into Biogas in Mungka District, Lima Puluh Kota Regency - Trisna Kumala Sari; Syamsi Aini; Edi Nasra; Riga Riga; Edwina Zainal (Pelita Eksakta, 2021)
The people of Jorong Padang Koto Tuo, Mungka District, Lima Puluh Kota Regency are increasingly enthusiastic about quail farming. The more developed the livestock business, the more manure is produced. This will certainly become a serious environmental problem, if not immediately followed up. Therefore, it is necessary to take action to treat this manure, including the use of appropriate technology for processing quail manure into biogas and fertilizer. This activity focused on educating the people of Jorong Padang Koto Tuo, Mungka District, Lima Puluh Kota Regency regarding the processing of quail waste into biogas as an alternative energy source that is environmentally friendly and inexpensive, starting from the tools, how the stages of work, what processes occur and the products produced. This activity not only has a good impact on the environment, but the resulting product can be used as a substitute for LPG gas. The people looks enthusiastic in participating in this activity.